To Kill a Mockingbird: The stunning graphic novel adaptation - Lee, Harper, Fordham, Fred (London William Heinemann, 2018)
'Shoot all the bluejays you want, if you can hit 'em, but remember it's a sin to kill a mockingbird.' A haunting portrait of race and class, innocence and injustice, hypocrisy and heroism, tradition and transformation in the Deep South of the 1930s, Harper Lee's To Kill a Mockingbird remains as important today as it was upon its initial publication in 1960, during the turbulent years of the Civil Rights movement. Now, this most beloved and acclaimed novel is reborn for a new age as a gorgeous graphic novel. Scout, Jem, Boo Radley, Atticus Finch and the small town of Maycomb, Alabama, are all captured in vivid and moving illustrations by artist Fred Fordham. Enduring in vision, Harper Lee's timeless novel illuminates the complexities of human nature and the depths of the human heart with humour, unwavering honesty and a tender, nostalgic beauty. Lifetime admirers and new readers alike will be touched by this special visual edition.